2019
DOI: 10.1017/s109285291800161x
|View full text |Cite|
|
Sign up to set email alerts
|

Unconjugated bilirubin and schizophrenia: a systematic review

Abstract: Schizophrenia is a complex syndrome of unknown etiology and difficult to manage. Unconjugated bilirubin has been researched as a potential biological marker of this syndrome. The objective of this review article was to gather the studies published to date on the relationship between this molecule and schizophrenia. Broad inclusion criteria have been used (PRISMA) to include as many relevant studies as possible. Fourteen studies were selected: 3 analyzed the effects of unconjugated hyperbilirubinemia in animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 80 publications
3
11
0
Order By: Relevance
“…In conclusion, we support the vision of the pathological spectrum of psychoses, 1 providing the genetic factor as a possible interpretation key. In fact, it has been described that the mean bilirubin level of patients with schizophrenia could be in the reference interval, and the frequency of GS is significantly higher in patients with schizophrenia 12 .…”
Section: To the Editorsupporting
confidence: 80%
See 1 more Smart Citation
“…In conclusion, we support the vision of the pathological spectrum of psychoses, 1 providing the genetic factor as a possible interpretation key. In fact, it has been described that the mean bilirubin level of patients with schizophrenia could be in the reference interval, and the frequency of GS is significantly higher in patients with schizophrenia 12 .…”
Section: To the Editorsupporting
confidence: 80%
“…We read with great interest the recent systematic review in your journal, which gathers the studies on the relationship between unconjugated bilirubin (UCB) and schizophrenia 1 . The authors, based on the articles they cited, support the existence of a correlation between UCB and schizophrenia, but point out that the relationship between the two is not clear.…”
Section: To the Editormentioning
confidence: 99%
“…It is therefore important to analyze its hypothetical role as a biological risk factor, linked with psychotic acute phases, thus making it eligible as a possible tool for early diagnosis, subsequent followup and even a target for new treatment strategies. 23 In this study, our main objective is to assess patients suffering from acute psychosis, trying to understand if UCB mean levels may have any potential interest as a biomarker in both categorical nosological axis (SCZ vs. SAF disorder) and a severity axis (relapse vs. partial remission). Our first hypothesis is that UCB levels will be higher in patients with SCZ than in patients with SAF disorder.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, UCB levels are clearly lower in patients with acute psychotic episodes of the schizophrenia when compared with healthy controls. Pommerening Dornelles et al ( 25 ) pointed out that studies reporting the lower UCB levels in schizophrenia ( 21 , 24 ) could indicate a chronic proinflammatory state caused by elevated reactive oxygen species and the consumption of the antioxidant potential, hence leading to neuronal damage. The study presented in this paper is the first to investigate the relation between peripheral biomarkers of inflammation derived from CBC and UCB levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inflammation, oxidative stress plays a key role in the progression of schizophrenia, while bilirubin is a strong endogenous antioxidant ( 45 ). A systematic review ( 25 ) showed that UCB is in part implicated in the pathophysiological process of schizophrenia, and elevated bilirubin may be linked with lower risk of schizophrenia in the acute stage. One recent study ( 46 ) showed potential of UCB as a biological marker for schizophrenia.…”
Section: Discussionmentioning
confidence: 99%